Importance of dental care in palliative care of cancer patients: an integrative literature review (Research, Society and Development, 2022)
The aim of this study was to highlight the role of the dentist in palliative care of adult cancer patients. This is an integrative review with search on PubMed, SciELO, Scopus, LILACS and Embase platforms. Primary articles published between 2010 and 2022 in English and Portuguese were included. Studies not directly related to the topic were excluded. Among 550 articles found, 11 were selected. Regarding the treatment of cancer patients, therapies such as surgery, radiotherapy and chemotherapy harm oral health, causing the appearance of oral manifestations during and after therapies, with the following problems being more frequent: xerostomia, mucositis or stomatitis, candidiasis, post-radiotherapy caries and osteoradionecrosis. In this sense, dental management is responsible for preventing and treating such complications, and pre-therapeutic evaluations and procedures are essential, as well as education in oral hygiene and periodic consultations with the dentist. The dentist's role is also to prevent opportunistic infections, which are frequent due to immunosuppression caused by radiotherapy or chemotherapy, reducing hospital stay and medication use. In addition, patients may have difficulty swallowing and breathing, as well as aesthetic and phonetic impairment, requiring rehabilitation with prosthetic devices. The dental role in palliative care in cancer patients is very important to promote a better quality of life, in view of the needs in oral care that arise during all stages of treatment. Insufficient training in undergraduate courses makes it difficult for dental surgeons to work in palliative care teams for cancer patients.